1991
DOI: 10.1126/science.252.5010.1293
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Observations of Bright and Dark Emission Features on the Night Side of Venus

Abstract: Near-infrared spectra of a bright and a dark thermal emission feature on the night side of Venus have been obtained from 2.2 to 2.5 micrometers (microm) at a spectral resolution of 1200 to 1500. Both bright and dark features show numerous weak absorption bands produced by CO(2), CO, water vapor, and other gases. The bright feature (hot spot) emits more radiation than the dark feature (cold spot) throughout this spectral region, but the largest contrasts occur between 2.21 and 2.32 microm, where H(2)SO(4) cloud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 16 publications
(13 reference statements)
1
16
0
Order By: Relevance
“…These bands are shifted from the longer wavelengths of their condensed phase within the cloud layers. Apart from one early study which found large variation in sub-cloud water vapour abundance, anti-correlated to cloud opacity [Bell et al, 1991], Earth-based observers [de Bergh et al, 1995;Marcq et al, 2006;Crisp et al, 1991] have not detected any spatial variation in sub-cloud water vapour. However, the instruments used in these observations had spatial resolutions of $500-2500 km at Venus and so would be unable to detect variations on smaller spatial scales.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…These bands are shifted from the longer wavelengths of their condensed phase within the cloud layers. Apart from one early study which found large variation in sub-cloud water vapour abundance, anti-correlated to cloud opacity [Bell et al, 1991], Earth-based observers [de Bergh et al, 1995;Marcq et al, 2006;Crisp et al, 1991] have not detected any spatial variation in sub-cloud water vapour. However, the instruments used in these observations had spatial resolutions of $500-2500 km at Venus and so would be unable to detect variations on smaller spatial scales.…”
Section: Introductionmentioning
confidence: 80%
“…We therefore follow a two-stage process to fit the spectra: first we retrieve cloud opacity by matching the 2.20-2.30 mm region of the spectrum, and secondly we retrieve the minor gas abundances using the 2.30 -2.50 mm spectrum. It is important to first fix the cloud structure before retrieving the gas abundances, because the cloud scattering properties are wavelength dependent and therefore affect the retrieved abundance of H 2 O [Bell et al, 1991;Marcq et al, 2006]. The CO, H 2 O and OCS abundances are retrieved simultaneously by minimizing the difference between the modelled synthetic spectra and the observed spectra Tsang et al, 2008aTsang et al, , 2008b.…”
Section: Methodsmentioning
confidence: 99%
“…This conclusion however, contradicts the results of a recent re-analysis of spectrophotometry on the Venera descent probes (Ignatiev et al 1997) and observations in the near IR windows (Crisp et al 1991b;de Bergh et al 2006;Bezard et al 2009Bezard et al , 2011 which imply an H 2 O mixing ratio of ∌30 ppm without significant latitude variability below the clouds. Bell et al (1991) report no detection of variability water vapor in the deep atmosphere, but other the near IR observations show that there is significant spatial variability of the cloud opacity, with persistently low optical depths at latitudes between 40 and 60° (Crisp et al 1991b). The low cloud optical depths at latitudes where the Pioneer Venus North Probe entered the atmosphere may explain the large thermal net flux divergences near the cloud base inferred from the net flux radiometer results .…”
Section: Radiation Field Inside the Atmospherementioning
confidence: 99%
“…Utilizing the thermal radiation produced by the planet's hot lower atmosphere to backlight overlying cloud structures near the 50-km level, these observations in the CO 2 -free spectral windows at 1.7 and 2.3 ”m revealed the spatially inhomogeneous nature of Venus' tropospheric clouds. Further analysis of these and subsequent spectroscopic and imaging observations from both the ground and the Galileo spacecraft (e.g., Kamp et al 1988;Kamp and Taylor 1990;Crisp et al 1989Crisp et al , 1991aCrisp et al , 1991bBĂ©zard et al 1990;Bell et al 1991;Carlson et al 1991Carlson et al , 1993bPollack et al 1993;Collard et al 1993;Drossart et al 1993;Grinspoon et al 1993;deBergh et al 1995;Taylor 1995) clearly demonstrated the usefulness of this new tool for measuring not only the spatially-varying particle sizes and opacities of these middle-level cloud structures near 48-57 km altitude, but also the cloud-tracked windfield and the latitudinally-varying chemical composition of the underlying deep atmosphere.…”
mentioning
confidence: 95%
“…In February 1990, both the Galileo spacecraft (Carlson et al 1991) and ground-based observers (Crisp et al 1991) measured radiation emitted by the lower atmosphere and surface at 1.01, 1.10, 1.18, 1.26, and 1.31 ”m. The 1.18-”m full-disk map of Venus's nightside obtained by the Galileo NearInfrared Mapping Spectrometer (NIMS) for the first time revealed many topographic features at optical wavelengths, including Maxwell Montes (Carlson et al 1991), Gula Mons, and Aphrodite Terra (Carlson et al 1993a).…”
mentioning
confidence: 99%